Insights of young entrepreneurship aspirants towards sustainable entrepreneurship in Malaysia - Elochukwu, Chekwube Cyprian (2023)
This research was aimed to study the relationship between eco-friendly people, green marketing factors, changing consumer behaviour and favourable market conditions towards sustainable entrepreneurship intention of young-adults in Malaysia. The target respondents for this research was undergraduate and graduates’ students of Fam faculty, UTAR, who are aged between 18 years old and 45 years old. The survey questionnaire was distributed to 250 participants through online social media WhatsApp. The data was collected and 200 response was valid and selected for the research. The respondent’s data was analysed using SPSS version 26, for the reliability and validity of the items used for study using Cronbach’s alpha. Also, the descriptive analysis, Pearson correlation analysis, and multiple regression analysis was tested. The outcome of the findings shows that all the four variables comprises of eco-friendly people, green marketing factors, changing consumer behaviour and favourable market conditions has positive and significant impact to sustainable entrepreneurship intention. Managerial implication of the study was discussed to give an insight on how these findings obtained will affect entrepreneurial activities and managers decision making process. Finally, the limitations for this study was stated and various recommendation was given for future researchers to improve.